Ruling Party’s Influences and The Re-Run Elections in Nigeria (Universitas Negeri Semarang, 2022)
Little attention was given to re-run elections in the previous studies; therefore, this study examined how the ruling party influenced the re-run elections in Nigeria. Through mixed-methods, our study discovered that the national ruling party won 93.1% of the re-run elections unlike 53.9% in general elections. Through 3-created models, we found undue influences on election process, institution and enforcement and civil election monitoring. They indirectly appointed, controlled, and determined the postings of major electoral agencies that were directly organized the pre, during and post-elections processes. State’s public facilities and workers were serving their interests and this created a strained relationship between the opposition parties and electoral agencies. Communities in opposition strongholds witnessed low voter-education, limited campaign time, poor registration of voters and inexperienced staff mainly to discourage full participation. Harmonizing the conduct of re-run elections with the general elections is necessary to limit the influence of the ruling party.